TI_GERICHTE 14.2011.105 vom 19. August 2011 , Reclamo contro la dichiarazione di fallimento. Nova in senso prorprio - TI Tribunale d'appello (2011)
Reclamo contro la dichiarazione di fallimento. Nova in senso prorprio